2019
DOI: 10.1016/j.jses.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Proximal humeral bony adaptations with a short uncemented stem for shoulder arthroplasty: a quantitative analysis

Abstract: BackgroundShort uncemented stems have recently been proposed as an alternative to classic long stems for shoulder arthroplasty. The early results are promising, but bony adaptations of the proximal humerus have been reported. The aim of this study was to quantify these phenomena using the Ascend Flex stem and to determine the risk factors.Materials and methodsIn a retrospective, single-center study, 183 shoulder arthroplasties were evaluated at 2-year follow-up. All patients underwent clinical evaluations preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 24 publications
2
36
1
Order By: Relevance
“…Five studies evaluated the phenomenon of subsidence between 2014 and 2019 for reverse USSPs [ 22 , 27 , 37 , 38 , 39 ]. Atoun et al [ 22 ] examined the radiographic outcome including subsidence of a reverse USSP (Verso; Biomet, Swindon, UK) in 31 patients after a mean follow-up of 36 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies evaluated the phenomenon of subsidence between 2014 and 2019 for reverse USSPs [ 22 , 27 , 37 , 38 , 39 ]. Atoun et al [ 22 ] examined the radiographic outcome including subsidence of a reverse USSP (Verso; Biomet, Swindon, UK) in 31 patients after a mean follow-up of 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…No case of subsidence occurred at final follow-up of a minimum of two years. Peduzzi et al [ 39 ] evaluated the radiological outcome including subsidence of 81 shoulders after surgical treatment with a reverse USSP (Tornier Ascend TM Flex Shoulder System, Memphis, TN, USA) at a minimum follow-up of 24 months, but no case of subsidence was present. Again, all studies evaluated the radiographic outcomes only at short-term follow-up and neither subsidence nor aseptic loosening was described as a potential “risk” within this timeframe.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies reported on pain improvement from preoperative until the final FU using the Constant score (CS, 0 ¼ worst, 15 ¼ best) as an instrument for pain determination. 5,20,36,40,48 In four of these studies the pain score improved significantly. 2,20,40,48 Weighted means changed from 5.4 to 12.9 points at final FU.…”
Section: Clinical Outcomementioning
confidence: 91%
“…5,20,36,40,48 In four of these studies the pain score improved significantly. 2,20,40,48 Weighted means changed from 5.4 to 12.9 points at final FU. The standard visual analog scale (VAS; 0 ¼ best, 10 ¼ worst) was used to determine pain by Merolla et al 36 who reported significant improvement (8.5 to 0.8).…”
Section: Clinical Outcomementioning
confidence: 91%
See 1 more Smart Citation